Fast folding dynamics of small proteins: placing limits on diffusional limits - Hagen, Stephen (Henry Stewart Talks, 2007)
Basic time scales and diffusional limits in protein folding, Applying reaction rate theories to folding, Kramers behavior and friction, Internal friction of polymer chains, Evidence for (or against) internal friction in protein folding, Fast folding experiments and methodology, Interpretations: internal time scales versus internal viscosity, Limitations of the "diffusional limits" picture
Archived at 2020/08/13